Program Ecovillage sebagai Upaya Perubahan Perilaku Masyarakat dalam Pelestarian Lingkungan Menurut Perspektif Islam: Studi Kasus Ecovillage di Desa Banjarwaru - Diana Ferginia; Riyadi Yanto (ALIF, 2022)
Ecovillage is a village with an environmental culture where the people are able to manage the environment well. Ecovillage as a form of human interaction with the environment to achieve sustainability, with development activities. A village that aims to facilitate the community in managing environmentally friendly waste crushing machines and facilitating the waste management process that does not pollute the environment. With the application of the ecovillage concept, it can be seen that people's behavior in creating a better environment, community cooperation is formed, and there is a sense of care for the environment with the existence of the waste crushing machine/machine. This study aims to examine the ecovillage program as an effort to change people's behavior in environmental preservation according to an Islamic perspective. This study takes an ecovillage case study in Banjarwaru Village. The method used in this research is a qualitative method. Where the object of this research is the waste crushing machine, the person in charge of the ecovillage, the village staff, the Head of RW 5, and residents around Banjarwaru Village. The primary data collection technique was carried out using purposive sampling through interviews, observation, and field practice. Based on the research results, it can be concluded that environmental conservation studies based on ecovillage have good value in the ecological, economic, and social dimensions of society. Factors that need to be improved may be socialization to the local community so they care more about the condition of the surrounding environment. The ecovillage program held in Banjarwaru Village is good enough to be introduced to a wider audience.